Overview of Securitization in the Dynamics of Relations between Saudi Arabia and the Muslim Brotherhood Post-Arab Spring - Kalbuadi, Rifan (Indonesia Center for Middle East Studies, 2020)
In March 2014, Saudi Arabia, through a royal decree, designated the Muslim Brotherhood (MB) as a terrorist organization. This decision has influenced the geopolitical dynamics of the Middle East to this day as Saudi Arabia is one of the strongest actors in the region. The designation of MB as a terrorist organization was a response from the Saudi government to MB's involvement in the Arab Spring 2011 and the Saudi allegations of MB's involvement in the removal of Egyptian President Hosni Mubarak and various anti-government protests that spread in several Middle Eastern countries. The Saudis did not always see MB as a threat. There was a time when the relationship between the two had occurred in harmony so that in this case, there had been a shift in perception. This paper analyzes this phenomenon using the theory of securitization by including the components of securitization as a framework for analysis. The author argues that the strengthening of MB on the political scene of the Middle East with its efforts to implement modernist Muslim ideology and offer democracy through a revolution is the cause of the shift in the perception of Saudi Arabia towards MB.